Percepto-motor development in sheltered children and not sheltered - Suehiro, Adriana Cristina Boulhoça; Rueda, Fabián Javier Marín; Silva, Marlene Alves da (Paidéia (Ribeirão Preto), 2007)
This study explored eventual differences in the development of sheltered and non-sheltered children through the Bender Gradual Scoring System(B-SPG). The following variables were considered: gender, age and pictures' difficulty. A total of 128 children, both genders, average age of 8,80 years (DP=0,99), equally distributed regarding housing types were studied. The nine Bender's pictures were collectively applied in a single session. The results indicate that non-sheltered children presented significantly higher scores compared to the sheltered ones. A statistically significant difference was evidenced regarding age only for the sheltered participants, whereas, significant differences between genders for both housing types were not found. The need of other studies for future comparisons regarding figures' difficulty was verified. Likewise, further research should be carried out with B-SPG, especially because it is a new system for a test extensively used for a long time.